Hubungan Motivasi Kerja Dengan Kepuasaan Kerja Perawat - Nina Fentiana; Daniel Ginting (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Motivation is important because motivation is something that causes, distributes and supports human behavior so that they want to work hard and enthusiastically to achieve optimal results. This study aims to determine the relationship between work motivation and nurse performance. The type of research used is Quantitative Research using a Cross-Sectional approach. Samples were taken as many as 87 nurses at Panyabungan Hospital. Data analysis used the Chi-square test at a significance level of α <0.05. There is a relationship between work motivation and nurse job satisfaction. is expected to increase positive attention to the assessment of work performance, increase self-motivation to achieve the achievements achieved..